2010
DOI: 10.3748/wjg.v16.i48.6068
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase system in hepatic ischemia-reperfusion injury

Abstract: Hepatic ischemia-reperfusion injury (IRI) limits access to transplantation. Heme oxygenase-1 (HO-1) is a powerful antioxidant enzyme which degrades free heme into biliverdin, free iron and carbon monoxide. HO-1 and its metabolites have the ability to modulate a wide variety of inflammatory disorders including hepatic IRI. Mechanisms of this protective effect include reduction of oxygen free radicals, alteration of macrophage and T cell phenotype. Further work is required to understand the physiological importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 122 publications
(134 reference statements)
0
24
0
Order By: Relevance
“…Therefore, a potential role for biliverdin and carbon monoxide as inhibitors of viral replication (via their antioxidative effects) requires further study [53] . Recent advances in molecular biology have provided new approaches to reducing hepatic IRI with gene therapy [55] . Liver transplantation [56] (a commonly employed treatment for hepatic failure) is still a limited means of therapy and has many drawbacks, including high monetary costs for the patient and donor shortages [8] .…”
Section: Ho-1 As a Potential Therapeutic Target In Liver Diseasesmentioning
confidence: 99%
“…Therefore, a potential role for biliverdin and carbon monoxide as inhibitors of viral replication (via their antioxidative effects) requires further study [53] . Recent advances in molecular biology have provided new approaches to reducing hepatic IRI with gene therapy [55] . Liver transplantation [56] (a commonly employed treatment for hepatic failure) is still a limited means of therapy and has many drawbacks, including high monetary costs for the patient and donor shortages [8] .…”
Section: Ho-1 As a Potential Therapeutic Target In Liver Diseasesmentioning
confidence: 99%
“…Heme oxygenase-1 (HO1), the rate-limiting enzyme in heme degradation with a strong anti-inflammatory and antiapoptotic role, can protect against various injuries, such as ischemic-reperfusion injury [4]. However, the advantages in anti-apoptotic and cytoprotective roles of HO-1 turn out to induce tumor-progression in cancer chemotherapeutic [5].…”
mentioning
confidence: 99%
“…Literature data indicate that supplementation with L-arginine has beneficial effect in clinical conditions observed in impaired endothelial function, increased production of oxygen free radicals, increased lipid peroxidation and, consequently, damage to multiple organs [23,26]. Many studies have revealed a positive improvement of endothelial function after administration of L-arginine to smokers, patients with idiopathic mild hypertension, patients with pregnancy-induced hypertension and patients with hypercholesteremia [9,16,18,25].…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals damage can lead to destruction of cell membrane structures. The level of ischemia-reperfusion damage can be assessed by determining the characteristic parameters for a given tissue, which normally occur in the blood serum in small amounts and after damage to cellular structures "leak" into the blood [1,23].…”
Section: Introductionmentioning
confidence: 99%